Między poczuciem akceptacji, wsparcia a wykluczeniem – uwarunkowania różnych dróg adaptacji dzieci do szkoły - Farnicka, Marzanna; Liberska, Hanna (Wydawnictwo Naukowe UAM, 2017)
The present study includes selected conditions of adaptation to the school. The research question focused on different predictors of sense of acceptanceand self-esteem and a sense of exclusion. The study involved 270 children aged 8-12. Data were collected twice using two tools: a questionnaire SUSPO and QSL. The results showed dynamic processes and differences occurring in the first and the second period of primary education and the opportunity to create conditions for a successful learning environment by the teacher.
Between a Sense of Acceptance and Exclusion – Indicators of Different Developmental Paths of Lives in School
Keywords: pupils; primary – education; adaptation; exclusion; acceptation